The need for improvement of cooperation between regional executive institutions in a context of possible notorious emergency situations in Ukraine - Orlov, М. М. (Honor and Law, 2019)
Performed brief analysis of notorious emergencies that could happen in Ukraine, described the need for improvement of cooperation between regional executive institutions in a field of law enforcement and gave directions for creation of efficient cooperation system